SPECIFIC CHARACTERISTICS OF WORKING WITH GRIM IN VARIETY - Djalilova Feruza Suratovna (Western European Studies, 2024)
Make-up techniques in pop, circus, dramatic theater of various genres. Pop art requires direct communication between the actor and the audience. A variety theater actor assumes that the viewer has a sense of humor, that he must understand the character of the comedy. The process of laughing at flaws requires the actor to communicate directly with the audience in order to encourage the actor to act. Laughing at flaws is a sign that a person is getting morally healthy. When using exaggeration, a pop actor should have a very sensitive sense of the norm. Charlie Chaplin said about it: "I'm afraid of exaggerating too much or touching someone's sensitive spot. Exaggeration can only be smoothed out with a good laugh." The uniqueness of the variety actor is seen in the combination of drama and comedy, tragedy and eccentricity. An example of this is the work of Charlie Chaplin, the great actor of the 20th century.
Keywords: example; tragedy; eccentricity